The Role of The Pancakarya Village Government in Structuring Land Ownership to Prevent Agrarian Conflicts - Akbar, Muhammad Gary Gagarin; Abdillah, Rafialdi; Fadillah, Mochammad Adi Alamsyach; Bintang, Muhammad; Sanaky, Safitri; Nurazizah, Rizka Amelia; Aditia, Fani (Jurnal Hukum dan Keadilan, 2024)
This study examines the role of the Pancakarya Village government in structuring land ownership to prevent agrarian conflicts. Using normative juridical methods, this study analyzes the process of transferring land ownership according to the Basic Agrarian Law (UUPA) and the role of village governments in protecting communities from inequality in land ownership. The results of the study show that the Pancakarya village government has succeeded in accommodating 90% of the community in the land certificate whitening program. However, there are still obstacles such as land boundary conflicts and lack of public understanding of the importance of certificates. The village government plays a role as a mediator in resolving disputes and conducting socialization related to the land certification program. This study recommends several improvement steps, including optimizing the use of land ownership master books, integrating data with digital land information systems, and increasing cooperation with the National Land Agency (BPN). These steps are expected to increase legal certainty and reduce the potential for agrarian conflicts in Pancakarya Village.